Śatacaṇḍīyāgavidhiḥ arthāt Caṇḍīyāgavidhiḥ: śatacaṇḍī, sahasracaṇḍī aura lakṣacaṇḍīyāga kī sampūrṇa vidhiyoṃ kā samāveśa - Gauḍa, Aśoka Kumāra (Vidyābhavana prācyavidyā granthamālā, 2010)
Collection of hymns and rituals for the worship of Caṇḍī, Hindu deity